Bhakti and Power: Debating India’s Religion of the Heart, edited by John Stratton Hawley, Christian Lee Novetzke and Swapna Sharma - Killingley, Dermot (Religions of South Asia, 2023)
Bhakti and Power: Debating India’s Religion of the Heart, edited by John Stratton Hawley, Christian Lee Novetzke and Swapna Sharma. Seattle, WA: University of Washington Press, 2019. xii + 255 pp. ISBN 9780295745503 (pb).